ANALISIS KADAR MERKURI (Hg) DALAM AIR SUNGAI MENGGUNAKAN METODE COLD VAPOR-ATOMIC ABSORPTION SPECTROPHOTOMETRY (CV-AAS) - Margaretta D. R. N. S; Subur P. Pasaribu; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Analysis of mercury (Hg) levels in river water using the cold vapor-atomic absorption spectrophotometry (CV-AAS) method has been carried out. The basic principle of determining Hg in several river water samples is carried out by means of Hg2+ ions being reduced by reductants Sn2+ into gaseous Hg0 atoms, and then the Hg0 atomic vapors were analyzed quantitatively by the CV-AAS method at a wavelength of 253.7 nm. The analytical performance of the measurements obtained was very good, indicated by the linearity value (r) = 0.991, the Quality Control (QC) value) Hg is below the standard, which is 10%, and the results of mesurement of Hg levels in water samples around range concentration was -1.0305 sampai -0.7328 ppb. These results indicate that the Hg level in river water, according to Government Regulation No. 22 of 2021 concerning Implementation of Environmental Protection and Management, is below the threshold of the quality standard. Keywords: Hg, cold vapor-atomic absorption spectrophotometry (CV-AAS), River waters